Analisis Gaya Bahasa Senryuu dalam Anime “Senryuu Shoujo” Karya Masakuni Igarashi - Jovan Dzulfikar Pranata; Eva Amalijah (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
Abstract. Language is an arbitrary system of voice symbols used by members of social groups to collaborate, communicate and identify. Style of language is part of language. Language style is the way that the author expresses their ideas in accordance with the purpose and outcome they wants to achieve. This study of the language style analyzed Masakuni Igarashi's "Senryuu Shoujo" Anime that tells of Shiroyuki Nanako who can only communicate through Senryuu. The study used descriptive analysis methods and stylistically approaches to describe the meaning of Senryuu in the Anime. From the 2 episodes that have been analyzed, 22 are collected and classified according to the language style. By performing a descriptive analysis method the results obtained are Senryuu with 4 Sinekdot, 10 Metamora, 6 Hyperbola, and 2 Simile, respectively. The linguistic style classification of this study is consistent with the theory of Seto Ken'ichi (瀬戸賢一(せとけんいち)) (Seto, 2002) Keywords: Language Style, Senryuu, Stylistic, Anime Abstrak. Bahasa adalah sistem simbol suara yang sewenang-wenang yang digunakan oleh anggota kelompok sosial untuk berkolaborasi, berkomunikasi dan mengidentifikasi. Di dalam bahasa terdapat Gaya bahasa. Gaya bahasa merupakan cara yang digunakan pengarang dalam memaparkan gagasannya sesuai dengan tujuan dan hasil yang ingin diperoleh. Penelitian tentang gaya Bahasa ini menganalisis tentang Anime “Senryuu Shoujo” ciptaan Masakuni Igarashi yang menceritakan tentang Shiroyuki Nanako yang hanya bisa berkomunikasi melalui Senryuu. Penelitian ini menggunakan metode analisis deskriptif dan pendekatan secara stilistika untuk mendeskripsikan makna Senryuu di dalam Anime tersebut. Dari 2 episode yang telah di analisis, terdapat 22 data yang terkumpul dan digolongkan sesuai dengan gaya bahasanya. Dengan melakukan metode analisis deskriptif hasil yang diperoleh berupa Senryuu dengan masing-masing terdapat 4 Sinekdot, 10 Metamora, 6 Hiperbola, dan 2 Simile. Pengelompokkan Gaya bahasa pada penelitian ini sesuai dengan teori dari Seto Ken’ichi (瀬戸賢一(せとけんいち)) (Seto, 2002) Kata Kunci : Gaya Bahasa, Senryuu, Stilistika, Anime